The electrode model of corona plasma discharge theory for current–voltage characteristics case in air - Wardaya, Asep Yoyo; Muhlisin, Zaenul; Suseno, Jatmiko Endro; Soesanto, Qidir Maulana Binu; Azam, Muchamad; Setiawati, Evi; Hadi, Susilo (European physical journal. Applied physics, 2022)
The calculation of the electrode model in the corona plasma discharge case has been carried out using the semi-ellipse line to plane (S-ELTP) configuration model in the air. The final focus of this research is to calculate the ( I – V ) current–voltage characteristics of the plasmas discharge. Part of the work in the ( I – V ) characteristics includes computational calculations and carrying out experimental activities. Experimental data include current vs voltage variations that occur at the time of plasma discharge. All the discharge processes are generated by a positive DC voltage source. The arrangement of the geometric configuration of the electrodes consists of two plates in the form of a half ellipse (active electrode) and a rectangular plate (passive electrode) in a mutually perpendicular position. The size variation of the active electrode includes variations of the small and large size plates with each plate having two variations in the distance between the two electrodes. The calculation concept of the electrode model is to insert the certain shape sharpness factor of k in the numerical calculation in the sharp electrode capacitance part. The k factor value is obtained by calculating the fitting between numerical simulation and research data. The research results prove that there is a fairly high level of conformity between numerical simulation and the research data. Simulation calculation for the ( I – V ) characteristic curve and its level of accuracy used Python GUI Programming.